2023
DOI: 10.1007/s12144-023-04369-8
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of psychological empowerment: Antecedents, organizational outcomes, and moderating variables

Abstract: Psychological empowerment (PE) is a subjective, cognitive and attitudinal process that helps individuals feel effective, competent and authorized to carry out tasks. Over the last twenty years, research into PE has reported strong evidence reaffirming its role as a motivational factor in organizational psychology. In this study, the aim is to systematically review, analyze and quantify correlational empirical research focusing on empowerment, as understood by the theory developed by Spreitzer et al. (1995a, b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…This sense of relatedness can provide social support, encouragement, and shared goals (Shah et al, 2019), which can further spur proactive behavior. Earlier empirical research has also confirmed a connection between PE and a range of favorable work-related results such as employee engagement (Nwachukwu et al, 2022), organizational trust (Kiziloglu et al, 2023), career satisfaction (Kong et al, 2016), OCB (Turnipseed and VandeWaa, 2020), job satisfaction and innovative behavior (Llorente-Alonso et al, 2023). There are also some incidences where PE has been associated with proactivity and OCB (Raub and Robert, 2007).…”
Section: Theoretical Underpinningsmentioning
confidence: 85%
“…This sense of relatedness can provide social support, encouragement, and shared goals (Shah et al, 2019), which can further spur proactive behavior. Earlier empirical research has also confirmed a connection between PE and a range of favorable work-related results such as employee engagement (Nwachukwu et al, 2022), organizational trust (Kiziloglu et al, 2023), career satisfaction (Kong et al, 2016), OCB (Turnipseed and VandeWaa, 2020), job satisfaction and innovative behavior (Llorente-Alonso et al, 2023). There are also some incidences where PE has been associated with proactivity and OCB (Raub and Robert, 2007).…”
Section: Theoretical Underpinningsmentioning
confidence: 85%
“…Leadership plays a pivotal role in spurring employee creativity, but formal rules, regulations and compensation greatly affect their motivation and creative performance (Llorente-Alonso et al , 2023). Among organizational aspects, the reward system, including FR, is particularly influential on employee motivation.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…This is due to the fact that when women begin to believe, they become aware of who they are, what is undesirable about their circumstances, and how they could be in a better one, as well as what is within their reach and what they could do to improve themselves, which happens when they are mentally sound. [8] So, psychologically empowering women might act as a key to a world of opportunity. We should focus on this since women can only think, make decisions and work for themselves if their minds and brains are fully enlightened.…”
Section: Literature Reviewmentioning
confidence: 99%